2022
DOI: 10.4236/eng.2022.142008
|View full text |Cite
|
Sign up to set email alerts
|

Application of Machine Learning Methods on Climate Data and Commercial Microwave Link Attenuations for Estimating Meteorological Visibility in Dusty Condition

Abstract: Accurately measuring meteorological visibility is an important factor in road, sea, rail, and air transportation safety, especially under visibility-reducing weather events. This paper deals with the application of Machine Learning methods to estimate meteorological visibility in dusty conditions, from the power levels of commercial microwave links and weather data including temperature, dew point, wind speed, wind direction, and atmospheric pressure. Three well-known Machine Learning methods are investigated:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…These studies include some of the most popular statistical models, such as linear regression (LR), poison regression (PR), and evolutionary polynomial regression (EPR). As machine-learning techniques, they use gradient boost trees (GB) [4][5][6][7] , Bayesian belief networks 8-10 , Support Vector Machines (SVMs) [11][12][13] and Arti cial Neural Networks (ANNs) 11,[14][15][16][17][18][19] . These studies have consistently found that ML models can provide valuable insights into the condition of these pipelines and help prioritize maintenance and repair efforts based on forecasting the failure rate of water pipes; however, ensemble approaches for water pipe leakage predictions have yet to be thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…These studies include some of the most popular statistical models, such as linear regression (LR), poison regression (PR), and evolutionary polynomial regression (EPR). As machine-learning techniques, they use gradient boost trees (GB) [4][5][6][7] , Bayesian belief networks 8-10 , Support Vector Machines (SVMs) [11][12][13] and Arti cial Neural Networks (ANNs) 11,[14][15][16][17][18][19] . These studies have consistently found that ML models can provide valuable insights into the condition of these pipelines and help prioritize maintenance and repair efforts based on forecasting the failure rate of water pipes; however, ensemble approaches for water pipe leakage predictions have yet to be thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%